PENGARUH TAMBAHAN PERBAIKAN PENGHASILAN DAERAH DAN TUNJANGAN PROFESI TERHADAP KINERJA GURU PEGAWAI NEGERI SIPIL DAERAH SMA/SMK DI KABUPATEN MUSI BANYUASIN - Yuliani Yuliani (AKUNTABILITAS, 2014)
Efforts to improve the performance of teachers have been anticipated by the government to give a reward in the form of incentives .Musi Banyuasin , the government has reprogrammed incentives Income Tambahan Perbaikan Penghasilan ( TPPD ),while the Indonesian government through Law No. 14 Year 2005 on Teachers and Lecturers, has set the Tunjangan Profesi provision to teachers who have been certified .This means that teachers certified PNSD in Musi Banyuasin besides getting Tunjangan Profesi also get Tambahan Perbaikan Penghasilan Daerah (TPPD). By mindless why we conducted research to determine how the Tunjangan Profesi and TPPD influence on the performance of teachers in Musi Banyuasin .Thus between the budget that has been set with the resulting performance can be measured effectiveness and efficient so that it can be accounted for. Research conducted on a sample of 149 teachers, principals, and students . Based on the analysis of data obtained R Square 0.997 ( 99.7 % ) .Of the value of the significance of the value of the dependent variable t-test teacher performance can be deduced that TPPD and Tunjangan Profesi partially or stimulants ( together ) positive influence and significance ( < 0.01 ) on teacher performance PNSD SMA / SMK in Musi banyuasin .However, some indicators related to the utilization of the TPPD and Tunjangan Profesi there are still weaknesses , hence the need for further research , especially with regard to the factors that influence it .